MENCEGAH KECANDUAN GADGET TERHADAP REMAJA MELALUI PENERAPAN NILAI-NILAI TASAWUF: Studi Kasus Posyandu Remaja di Kota Cirebon - Andika Prasetiawan; Abdul Basit Atamimi; Adang Darmawan Achmad (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2025)
This research discusses the influence of Sufism in reducing and overcoming gadget addiction among teenagers in the locus of Posyandu Remaja RW 2 Krucuk Cirebon. This research method uses qualitative methods with data collection instruments through interviews, observation, and documentation. This study is to determine the conditions and changes in the use of gadgets in adolescents before and after the application of Sufism values using Imam Al-Ghazali's tasawuf- akhlaqi theory. The results show that the application of Sufism values is very effective in reducing the intensity of gadget use among teenagers. Before the application of tasawwuf values, teenagers spent an average of 8-10 hours per day using gadgets. However, after the application of tasawwuf values, there was a significant decrease; ranging from the duration of gadget use, improving the quality of social interaction to the level of adolescent spirituality.